Effect of seawater ions on cyclopentane-methane hydrate phase equilibrium - Lv, Qiunan; Zang, Xueru; Li, Xiaosen; Li, Gang (Fluid Phase Equilibria, 2018)
In present work, phase equilibrium of cyclopentane-methane hydrate formed in different salt solution systems was studied using an orthogonal test method. The target ions including four cations (K+, Na+, Mg2+, Ca2+) and two anions (Cl-, SO42-) were employed. The experimental results showed that the equilibrium temperature of cyclopentane - methane hydrate decreased when four cations (K+, Na+, Mg2+, Ca2+) and two anions (Cl-, SO42-) were added. The equilibrium temperature decreased with the increase of ion concentrations. Analysis of variance suggested that cations presented a sequential inhibition effect on hydrate formation as follows: Mg2+ > Ca2+ > Na+ > K+, while Cl- ion had a much stronger hydrate inhibition effect than SO42- ion. The hydrate inhibition strength of an ion depended on the charge and radii of ion. The inhibitory effects of ions became intensified with the charge increased and radius decreased. And the radius of ions played a more significant role than charge of ions in altering hydrate phase equilibrium. (C) 2017 Published by Elsevier B.V.